2018
DOI: 10.1016/j.scitotenv.2018.03.184
|View full text |Cite
|
Sign up to set email alerts
|

Biomass production in the Lower Mississippi River Basin: Mitigating associated nutrient and sediment discharge to the Gulf of Mexico

Abstract: A watershed model was developed using the Soil and Water Assessment Tool (SWAT) that simulates nitrogen, phosphorus, and sediment loadings in the Lower Mississippi River Basin (LMRB). The LMRB SWAT model was calibrated and validated using 21 years of observed flow, sediment, and water-quality data. The baseline model results indicate that agricultural lands within the Lower Mississippi River Basin (LMRB) are the dominant sources of nitrogen and phosphorus discharging into the Gulf of Mexico. The model was furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Model parameterization and calibration methods have been detailed in Ha et al . The simulation period is 21 years from 1990 to 2010.…”
Section: Methodsmentioning
confidence: 99%
“…Model parameterization and calibration methods have been detailed in Ha et al . The simulation period is 21 years from 1990 to 2010.…”
Section: Methodsmentioning
confidence: 99%
“…However, this intensive production has resulted in considerable nutrient‐related water quality problems, both for Corn Belt region stream systems and further downstream, primarily due to the use of inorganic fertilizer and livestock manure nutrients on cropland (Rabotyagov et al 2012; Kling et al 2017; Bouska et al 2018; Christianson et al 2018; Jones, Nielsen, et al 2018; Turner and Rabalais 2019). The Upper Mississippi River Basin (UMRB) and Ohio‐Tennessee River Basin (OTRB) comprise much of the Corn Belt region and are major sources of exported nitrogen and phosphorus to the Mississippi River and the Gulf of Mexico (USEPA 2008; Demissie et al 2012; Wu et al 2012; Demissie et al 2017; Kling et al 2017; Panagopoulos et al 2017; Ha et al 2018). Monitoring data reported for the UMRB (Sprague et al 2011) and major Iowa watersheds (Jones, Nielsen, et al 2018) confirm continued high nitrate export to the Mississippi River.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Switchgrass can also provide many other benefits, including increased soil organic carbon (SOC) sequestration, improved wildlife habitats, reduced fertilizer input requirements, and thus lower greenhouse gas emissions from the soil. [12][13][14][15][16][17][18][19][20][21][22] Historical data have shown that high nitrate loss from agricultural cropland is a major source of nitrogen in the Mississippi River Basin, 19,[22][23][24][25][26][27] which is concentrated in the agricultural dominant Upper Mississippi River Basin [28][29][30][31] especially in the major Iowa watersheds. 8,32,33 The United States Environmental Protection Agency (USEPA) Hypoxia Task Force concluded that establishing riparian buffers could play a central role in nutrient reduction strategy for the Mississippi River, leading to a reduction of hypoxia zone in the Gulf of Mexico.…”
mentioning
confidence: 99%